The Relationship Between Knowledge Level and Attitudes Towards HIV/AIDS Prevention Among Public High School Students - Mahendra, Mhd Habib Dwi; Nuriyah; Erny Kusdiyah; Rina Nofri Enis (LPPM Universitas Jambi, 2025)
Background: Human immunodeficiency virus (HIV) is an infection that attacks the immune system, specifically white blood cells called CD4 cells. Acquired Immunodeficiency Syndrome (AIDS) is the final stage of HIV infection, which occurs when the immune system is severely damaged by the virus. The purpose of this study was to determine the relationship between knowledge levels and attitudes toward HIV/AIDS prevention behavior. Method: This study employed a descriptive design with a cross-sectional approach. The sample was obtained through random sampling, with a total of 502 respondents from grade 11 of public high schools in Jambi City. Data were analyzed using univariate and bivariate methods using the chi-square test. The research instrument used a structured questionnaire. Results: Of the 502 respondents, 119 students (51.1%) had a moderate to poor level of knowledge, while 170 students (33.9%) had a good level of knowledge. Regarding attitudes, 107 students (21.3%) showed fair to poor attitudes, and 177 students (35.3%) had good attitudes. There was a significant relationship between the level of knowledge and attitudes and HIV/AIDS prevention behavior among public high school students in Jambi City in 2024 (p < 0.001). Conclusion: The majority of students have less-moderate knowledge, mostly positive attitudes, but good behavior is still low, so educational intervention is needed to improve students' knowledge, attitudes and behavior.